The uncertainty in regional innovation policy: some ration-ales and tools for learning in policy making - Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
This paper deals with two major dilemmas in regional innovation policy making: The dilemma that theory does not provide sufficient answers for the formulation of specific innovation policy measures addressing the problem configurations of single regions and the dilemma that role models are used as a substitute for orientation. In order to support policy learning, different approaches like evaluation, the development of innovation strategies and regional foresight are discussed.
urn:nbn:de:0011-n-1021869
Keywords: 330; Innovationspolitik; Regionalpolitik; Theorie-Praxis-Problem; Lernprozess